2016
DOI: 10.1210/jc.2016-1437
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation Endproducts and Bone Material Strength in Type 2 Diabetes

Abstract: Bone material properties are impaired in postmenopausal women with T2D as determined by reference point indentation. The results suggest a role for the accumulation of AGEs to account for inferior BMSi in T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 51 publications
13
124
3
5
Order By: Relevance
“…In response to physiological doses of insulin, cultured osteoblasts show increased proliferation, collagen synthesis, alkaline phosphatase production, and glucose uptake [120] and hyperinsulinaemia following insulin administration stimulates osteoblast activity and increases mineral apposition rates in rats [121]. However, despite high bone mass in adults with type 2 diabetes, bone quality is impaired and fracture risk is high suggesting that in the hyperinsulinaemic state, bone quality is impaired [122, 123]. To date, there are no studies in children to determine whether changes in skeletal ‘integrity’ secondary to hyperinsulinaemia occur as a result of chronic exposure to high blood glucose and insulin resistance.…”
Section: The Impact Of Childhood Obesity On the Endocrine Environmentmentioning
confidence: 99%
“…In response to physiological doses of insulin, cultured osteoblasts show increased proliferation, collagen synthesis, alkaline phosphatase production, and glucose uptake [120] and hyperinsulinaemia following insulin administration stimulates osteoblast activity and increases mineral apposition rates in rats [121]. However, despite high bone mass in adults with type 2 diabetes, bone quality is impaired and fracture risk is high suggesting that in the hyperinsulinaemic state, bone quality is impaired [122, 123]. To date, there are no studies in children to determine whether changes in skeletal ‘integrity’ secondary to hyperinsulinaemia occur as a result of chronic exposure to high blood glucose and insulin resistance.…”
Section: The Impact Of Childhood Obesity On the Endocrine Environmentmentioning
confidence: 99%
“…Instead, elevated fracture risk is attributed to secondary deficits in the microarchitecture and in the material properties of the bone tissue, along with pathophysiological and genetic factors intrinsic to diabetes itself . Variables inherent to both T1D and T2D, including chronic hyperglycemia and glycemic variation, tissue‐specific accumulation of advanced glycation end‐products (AGEs), dysregulation of insulin‐like growth factor 1 (IGF‐1) bioavailability, variable insulin exposure (endogenous or exogenous), enhanced oxidative stress, changes in bone mineral and vitamin D homeostasis, and regional diabetic microvascular disease, undoubtedly all impact the skeletal quality in diabetes . Added to these variables is an increased propensity to falling, whether attributable to acute hypoglycemia, peripheral neuropathy, decreased visual acuity, or postural instability .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of PEN in skin and bone exponentially increase with age [45, 46], and these amounts may be closely related to each other. The material strength of the bones in patients with T2DM, as confirmed by microindentation, was inferior to the non-diabetic subjects and was significantly and inversely associated with the levels of skin autofluorescence [47], indicating that the bone accumulation of AGEs aggravates the material properties of bone. Cross-sectional and prospective clinical studies showed that increased serum and urinary PEN concentrations were related to an increased risk of fractures in patients with type 1 and type 2 diabetes mellitus [4850, 51•] (Table 1).…”
Section: Introductionmentioning
confidence: 99%